Incidence and etiologic factors responsible for anovulation in infertility cases - Singangutti, Rajeshwari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Chronic anovulation is a common cause of infertility. Anovulation leads to a long-term problem such as hyperandrogenism. Anovulation usually associated with amenorrhoea about 20% and oligomenorrhoea of women with ovulatory dysfunction. Present study was designed to assess the incidence and etiological factors responsible for anovulation in infertility cases. Methods: Study comprised of one hundred patients attending the outdoor clinic of the department for infertility either primary or secondary with regular and irregular menstrual cycles and patients of secondary amenorrhoea. Results: Among the total cases Polymenorrhoea was seen in 10% of cases, oligomenorrhea in 14% cases, secondary amenorrhoea in 3% and 73% cases had normal menstrual cycle. cervical mucus viscosity in ovulatory group to be low in 84.6% cases, moderate in 8.5% cases and high in 38% cases. In anovulatory cycles findings were reversed with viscosity at 14th day it was moderate in 27.27% and higher in 54.54% cases. Conclusions: Cervical mucus is a good indicator of the cyclical changes in ovarian hormonal as no false positive results were found. Endometrial biopsy is the mainstay in infertility studios as it provides information regarding the ovulating status.